2002
DOI: 10.1176/appi.ajp.159.8.1337
|View full text |Cite
|
Sign up to set email alerts
|

Double-Blind, Placebo-Controlled Study of Risperidone for the Treatment of Disruptive Behaviors in Children With Subaverage Intelligence

Abstract: Risperidone was effective and well tolerated for the treatment of severely disruptive behaviors in children with subaverage IQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
233
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 415 publications
(252 citation statements)
references
References 41 publications
(46 reference statements)
9
233
0
7
Order By: Relevance
“…However, on balance it seems that our lack of effect on the Continuous Performance Task is consistent with the findings reported by Troost et al (2006) and by Pandina et al (2007). There is no literature on seat activity in the context of performing cognitive tasks, but the reductions seen here seem entirely consistent with clinical reports of reduced overactivity with risperidone treatment (e.g., Aman et al, 2002; Research Units on Pediatric Psychopharmacology Autism Network, 2002). On balance, the studies conducted with adults having schizophrenia showed very mixed results insofar as memory is concerned, whereas we were unable to demonstrate enhancement or worsening of memory performance.…”
Section: Cognitive-motor Effectssupporting
confidence: 88%
See 2 more Smart Citations
“…However, on balance it seems that our lack of effect on the Continuous Performance Task is consistent with the findings reported by Troost et al (2006) and by Pandina et al (2007). There is no literature on seat activity in the context of performing cognitive tasks, but the reductions seen here seem entirely consistent with clinical reports of reduced overactivity with risperidone treatment (e.g., Aman et al, 2002; Research Units on Pediatric Psychopharmacology Autism Network, 2002). On balance, the studies conducted with adults having schizophrenia showed very mixed results insofar as memory is concerned, whereas we were unable to demonstrate enhancement or worsening of memory performance.…”
Section: Cognitive-motor Effectssupporting
confidence: 88%
“…Aman et al (2002) also saw reductions on all of these subscales in children with disruptive behavior disorders, whereas Snyder et al (2002) observed reductions in all except the Overly Sensitive subscale. In a sense, this is a form of internal validation, as the same behavioral changes (except for Overly Sensitive) were seen on the same subscales across all three studies.…”
Section: Behavioral Effectsmentioning
confidence: 92%
See 1 more Smart Citation
“…Risperidone was found to be well-tolerated and superior to placebo in reducing aggressive behaviors in children with CD [664-666]. Two large controlled trials found risperidone to be superior to placebo in ameliorating hostile and aggressive behavior in lower-functioning children with disruptive behavioral disorders [667,668]. …”
Section: Reviewmentioning
confidence: 99%
“…33,34 Those studies found that the most common adverse events were drowsiness, headache and weight gain. The symptoms of aggression were controlled in 3 to 4 weeks using a mean dose of 1.5 mg/day, which was effective in the control of aggression for the next six months when compared with the placebo group.…”
Section: Risperidonementioning
confidence: 99%